Factors affecting match running performance in elite soccer: Analysis of UEFA Champions League matches - Toni Modric; Sime Versic; Marko Stojanovic; Paweł Chmura; Marcin Andrzejewski; Marek Konefał; Damir Sekulic (Termedia Publishing House, 2022)
This study aimed to examine the independent effect of different match-related factors on match running performance (MRP) in elite soccer. Players' MRPs (n = 244) were collected during UEFA Champions League (UCL) group stage matches in the 2020-21 season. All MRP data were collected by the semi-automatic optical system InStat Fitness (InStat Limited, Limerick, Republic of Ireland). Match-related factors included match outcome, team quality, match location, opponent quality and difference in team quality, while MRP included cumulative and relative measures of total distance (TD and R-TD), low-intensity running (LIR and R-LIR) (≤ 4 m/s), moderate-intensity running (MIR and R-MIR) (4-5.5 m/s) and high-intensity running (HIR and R-HIR) (≥ 5.5 m/s). Linear mixed models were used to examine the collective effect of match-related factors on MRPs when controlling for between-player, between-playing position and between-team variation. The main findings were that match outcome was associated with reduced HIR (d = -0.38, p = 0.04), match location was associated with increased TD, R-TD, LIR and R-LIR (d = 0.54-0.87, all p < 0.01), while team quality, opponent quality and difference in team quality were not associated with MRP. These results show that (i) winning UCL matches was not strongly influenced by players' physical performance, (ii) away UCL matches were characterized by a slower match pace and greater match volume, and (iii) players' physical performance was similar irrespective of playing either in or against high- or low-quality teams. The findings from this study may help soccer coaches to ensure optimal physical preparation of players in elite soccer.